Pemetaan Lamun Mengunakan Machine Learning Dengan Citra Planetscope Di Nusa Lembongan - Devica Natalia Br Ginting; Sanjiwana Arjasakusuma (Jurnal Kelautan Tropis, 2021)
Seagrass is one community in benthic habitat that has tremendous benefits for the ecosystem, however the existence of seagrass has been frequently marginalized in recent decades. Seagrass beds functions as a blue carbon ecosystem which are able to absorb carbon higher than terrestrial vegetation. Therefore, it is important to detect and map the seagrass beds distribution to calculate the potential carbon uptake from seagrass. The seagrass mapping can be employed efficiently by using remote sensing imagery and the use of machine learning technology. This research aims to examine the utilization of PlanetScope imagery (3.7 m spatial resolution) for seagrass mapping and to subsequently examine, the effect of atmospheric corrections, sun-glint, and the water column corrections on the accuracy of seagrass mapping. In addition, this study also identified the cover changes in seagrass area from 2016 to 2021 in Nusa Lembongan. The study utilized the tree-based machine learning methods such as decision tree and random forest. The results showed that the best model accuracy was generated by using raw PlanetScope data the best model accuracy of 98% and classification accuracy of 94% from decision tree method. Based on the decision tree mapping using PlanetScope data for 2016 and 2021, there was a decline in the seagrass cover from 100.53 hectares to 97.31 hectares. Lamun merupakan salah satu dari ekosistem habitat bentik yang memiliki manfaat yang sangat besar namun sebagai ekosistem, kehadiran lamun sering dikesampingkan beberapa dekade terakhir. Fungsi padang lamun sebagai ekosistem karbon biru mampu menyerap karbon lebih tinggi dibandingkan vegetasi daratan. Karena itu, penting untuk mendeteksi dan memetakan informasi padang lamun untuk memperhitungkan serapan karbon oleh lamun. Pemanfaatan lamun dapat dilakukan secara cepat dan efisien dengan mengunakan  teknologi penginderaan jauh dan pemenfaatan teknologi machine learning. Penelitian bertujuan untuk mengkaji pemanfaatan citra PlanetScope untuk memetakan lamun dan selanjutnya menganalisis pengaruh kalibrasi atmosferik, sun-glint, dan kolom air terhadap akurasi pemetaan padang lamun. Selain itu, perubahan tutupan lamun tahun 2016 – 2021 di Nusa Lembongan juga dipetakan. Penelitian ini menggunakan metode machine learning berbasis pohon seperti decision tree dan random forest. Hasil penelitian menunjukkan akurasi model terbaik dihasilkan dengan menggunakan data mentah dengan akurasi model 98% dan akurasi klasifikasi 94% dari metode decision tree. Berdasarkan data PlanetScope tahun 2016 dan 2021 dengan mengunakan metode decision tree terjadi penurunan luasan lamun dari 100,53 Ha menjadi 97,31 Ha.